Impact of maternal gestational weight gain in twin pregnancies on early childhood obesity risk: A longitudinal birth cohort study - Li, Sisi; Qiu, Yuhan; Yuan, Xi; Zhang, Qin; Kilby, Mark D.; Saffery, Richard; Baker, Philip N.; Wen, Li; Tong, Chao; Qi, Hongbo (Frontiers in Pediatrics, 2022)
Objectives: To investigate the impact of gestational weight gain (GWG) on the body mass index-for-age z score (BAZ) and obesity risk among twin offspring. Methods: This study included 263 women who were pregnant with twins and their offspring. Maternal GWG was measured in each trimester, and infant weight and length were measured at 6, 12, and 24 months. Results: Total GWG was positively correlated with offspring birthweight and BAZ at 6, 12 and 24 months (adjusted β 0.013, (95% CI: 0.008-0.019), 0.028 (95% CI: 0.005-0.050), 0.033 (95% CI: 0.010-0.056) and 0.025 (95% CI: 0.004-0.047), respectively). Excessive total GWG was related to an increased relative risk (RR) of large for gestational age (LGA) and overweight at 6 and 12 months. Only the second trimester gestational weight gain rate (GWGR) was positively correlated with birthweight (adjusted β 0.380, 95% CI: 0.256-0.504), and RRs of 6.818 (95% CI: 1.568-29.642) and 2.852 (95% CI: 1.466-5.548) were found for LGA and overweight at 12 months, respectively. Conclusions: Total GWG and the second trimester GWGR were correlated with BAZ and overweight/obesity risk in twin offspring; the impact was obvious in the first year of life and gradually disappeared over time.